Legal Protection of Abandoned Land After the Enactment of Government Regulation Number 20 of 2021 Concerning the Management of Abandoned Areas and Land From the Perspective of Maqashid Syariah - Prajuliara, Dodek; Tarigan, Tetty Marlina (Yayasan Lembaga Studi Makwa, 2025)
Land has a strategic role in national development, both from economic, social, and cultural aspects. However, there are still many lands in Indonesia that have abandoned status because they are not used in accordance with the purpose of granting their rights. This condition raises legal and social problems, especially related to the certainty of rights, the social function of land, and the distribution of prosperity. The birth of Government Regulation Number 20 of 2021 concerning the Management of Abandoned Areas and Land is an important legal instrument to regulate land tenure in line with the principles of social justice and welfare as stipulated in the 1945 Constitution and the Basic Agrarian Law (UUPA). This study aims to analyze the legal protection of abandoned land after the enactment of Government Regulation No. 20 of 2021 and review it from the perspective of Maqashid Syariah. The research method used is normative juridical with a statutory approach and a conceptual approach, through the analysis of laws and regulations, legal literature, and secondary data related to abandoned land. The results of the study show that legal protection of abandoned land can be carried out through preventive and repressive mechanisms, both through regulation, socialization, and legal dispute resolution. From the side of Maqashid Sharia, the policy of controlling abandoned land is in line with the principles of ḥifẓ al-mal (protection of property) and ḥifẓ al-nasl (protection of descendants), because it ensures that land is used for the benefit of the community and is inherited fairly to the next generation. Thus, this regulation not only strengthens legal certainty, but also accommodates the value of social justice and the benefit of the people.